ANALISIS KAPASITAS SALURAN PADA DRAINASE JALAN IMAM BONJOL KELURAHAN PAMUSIAN DENGAN STORM WATER MANAGEMENT MODEL (SWMM) - Zunifa, Afara; Amiruddin, Aswar (Civil Engineering Scientific Journal, 2025)
An effective drainage system in urban areas is essential to manage flooding caused by heavy rainfall. Inadequate drainage channels cannot accommodate excess water, leading to water stagnation and other negative impacts. Therefore, calculating the design flood discharge and designing drainage channels with sufficient capacity are crucial for stormwater management. This study aims to evaluate the capacity of existing drainage systems to handle design flood discharge and to design new drainage dimensions that can accommodate the largest discharge. The analysis shows that most existing drainage channels are unable to accommodate the design discharge (Qt) for return periods of 10, 20, 50, and 100 years, as the channel discharge (Qs) is smaller than the design discharge. Simulations using the Storm Water Management Model (SWMM) identified critical points at Junction 4 and Junction 10, where overflow occurs due to excess channel capacity. As a solution, new drainage dimensions were designed. A rectangular channel with a bottom width of 1.2 meters and a height of 1 meter can carry the discharge without overflow for a 100-year return period. Meanwhile, a trapezoidal channel with a bottom width of 0.25 meters, a height of 0.8 meters, and a side slope of 0.618 meters is also effective in accommodating the design discharge without overflow. This study recommends increasing the drainage capacity at critical points to reduce the risk of water stagnation